The Effect of Time and Dose from Gamma Irradiation (Cesium-137) on Protein Levels and Meat Color Index of Cork Fish (Channa Striata) - Janna, Miftahul; Fuadi, Nurul; Jumardin, Jumardin; Sahara, Sahara; Isradianti, Dwi Febri; Hidayat, Serli Hatul (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The study aimed to determine the effect of time and dose of gamma-ray irradiation on protein levels and storability based on the red color index of cork fish (channa striata). The results showed that the longer the irradiation time and the larger the dose given, the higher the protein level and absorbance value produced. The method used was UV-Vis spectrophotometry to determine protein levels and Image-J software to see the shelf life based on the red colour index. The sample consisted of control, irradiated with irradiation time of 35 minutes (6 mGy), 40 minutes (7 mGy) and 45 minutes (8 mGy) and an irradiation distance of 150 cm. The protein levels at control time, which were recorded at 35, 40, and 45 minutes, were 0.138%, 0.187%, 0.276%, and 0.347%, respectively. These results suggest that there may be a correlation between time and protein levels. Further analysis may be needed to fully understand the implications of these findings. The percentage close to stable on the first day with percentages of 1.54%, 1.66%, 1.76%, 2.50%. Additionally, it seems that a higher dose of irradiation may also result in a higher protein content and absorbance value.Keywords: Cesium-137, Cork Fish, Irradiation, Protein, UV-Vis Spectrophotometer